2006
DOI: 10.1248/bpb.29.403
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Diagnostic Method for Chronic Hepatic Disorder: Analyses of Metallothionein Isoforms and Trace Metals in the Liver of Patients with Hepatocellular Carcinoma as Determined by Capillary Zone Electrophoresis and Inductively Coupled Plasma-Mass Spectrometry

Abstract: Metallothionein (MT) is a low molecular weight and cysteine-rich protein that binds to several heavy metals. The suggested functions of MT are detoxification of heavy metals, maintenance of trace element homeostasis, and scavenging of free radicals via the thiol groups present in the protein.1,2) Hepatocellular carcinoma (HCC) is one of the most common human tumors that occurs globally, and generally develops from chronic hepatitis (CH) and liver cirrhosis (LC). [3][4][5] It is, therefore, very important to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Beginning with Danielsen and Steinnis in 1970, 3 ten reported population studies [3][4][5][6][7][8][9][10][11][12] have consistently demonstrated a marked decrease (~55-75%) in zinc levels in HCC tissue compared with normal liver tissue. The "typical" results are represented in Figure 1 from Kew and Mallet, 7 who concluded that "the zinc concentration in the liver cancer tissue was significantly less than that in the non-cancerous tissues, whether cirrhotic or non-cirrhotic in the HCC patients or normal from the noncancerous patients (P < 0.001 in each instance)."…”
Section: The Status Of Zinc Levels In Hccmentioning
confidence: 99%
See 1 more Smart Citation
“…Beginning with Danielsen and Steinnis in 1970, 3 ten reported population studies [3][4][5][6][7][8][9][10][11][12] have consistently demonstrated a marked decrease (~55-75%) in zinc levels in HCC tissue compared with normal liver tissue. The "typical" results are represented in Figure 1 from Kew and Mallet, 7 who concluded that "the zinc concentration in the liver cancer tissue was significantly less than that in the non-cancerous tissues, whether cirrhotic or non-cirrhotic in the HCC patients or normal from the noncancerous patients (P < 0.001 in each instance)."…”
Section: The Status Of Zinc Levels In Hccmentioning
confidence: 99%
“…Similarly, Tashiro et al studies 4 concluded that "the Zn concentration in cancerous liver was lower (55% decrease) than in noncancerous liver tissue for all twenty-three subjects." Only one study (Ebara et al 13 ) had reported a zinc increase in HCC, which was subsequently reversed by pursuant studies of the Ebara group 5,6 that showed a consistent significant decrease in zinc in HCC. In addition, our studies 14 with tissue samples from 26 HCC cases identifies the specific zinc decrease in the hepatoma cells in well-differentiated and advancing malignancy, as compared to the higher zinc in the normal hepatocytes (Fig.…”
Section: The Status Of Zinc Levels In Hccmentioning
confidence: 99%
“…Excessive liver copper and iron accumulations are known risk factors for liver cancer. Indeed, greater copper levels with lower MT levels were noted in neoplastic liver samples, compared with surrounding non-neoplastic liver portions (Kawata et al 2006). The MT sequestration of cadmium is considered to provide protection against acute toxicity.…”
Section: Metallothionein Sequestration and Cadmium's Long Half-lifementioning
confidence: 99%
“…Cadmium, bound to the different rabbit-liver MT isoforms separated by CE, was postcapillary transformed into volatile species and online detected by ICP-MS. An ICPsector field-mass spectrometer was used for the determination of the stoichiometric Zn/protein ratio by monitoring both Zn and S after the CE separation of free Zn ions and the zinc bound to a metalloprotein [182]. Kawata et al [183] have presented a new diagnostic method for chronic hepatic disorder based on CE determination of MT isoforms and trace metals in the liver of patients. Other applications to real biological material (but with UV detection) encompassed the separation and determination of MT isoforms in rat liver cytosol [184] and horse kidney preparations [185] using polyacrylamide coated capillaries, and measuring induction of MTs in maize plantlets by chromium(VI) exposure [186].…”
Section: Hyphenated Techniquesmentioning
confidence: 99%